Anthropic and climatic impacts on biodiversity during the Mesolithic-Neolithic transition in North-Western France - Nathan Martin; Kevin Nota; Cédric Aumont; Grégor Marchand; Dominique Marguerie (Quaternary International, 2024)

Isolated Grauer's gorilla populations differ in diet and gut microbiome - Alice Michel; Riana Minocher; Peter‐Philip Niehoff; Yuhong Li; Kevin Nota; Maya A. Gadhvi; Jiancheng Su; Neetha Iyer; Amy Porter; Urbain Ngobobo‐As‐Ibungu; Escobar Binyinyi; Radar Nishuli Pekeyake; et al. (Molecular Ecology, 2023)
The animal gut microbiome has been implicated in a number of key biological processes, ranging from digestion to behaviour, and has also been suggested to facilitate local adaptation. Yet studies in wild animals rarely compare multiple populations that differ ecologically, which is the level at which local adaptation may occur. Further, few studies simultaneously characterize diet and gut microbiome from the same sample, despite their probable interdependence. Here, we investigate the interplay between diet and gut microbiome in three geographically isolated populations of the critically endangered Grauer's gorilla ( Gorilla beringei graueri ), which we show to be genetically differentiated. We find population‐ and social group‐specific dietary and gut microbial profiles and covariation between diet and gut microbiome, despite the presence of core microbial taxa. There was no detectable effect of age, and only marginal effects of sex and genetic relatedness on the microbiome. Diet differed considerably across populations, with the high‐altitude population consuming a lower diversity of plants compared to low‐altitude populations, consistent with plant availability constraining dietary choices. The observed pattern of covariation between diet and gut microbiome is probably a result of long‐term social and environmental factors. Our study suggests that the gut microbiome is sufficiently plastic to support flexible food selection and hence contribute to local adaptation.

Plants, pollinators and their interactions under global ecological change: The role of pollen DNA metabarcoding - Karen L. Bell; Katherine J. Turo; Abigail Lowe; Kevin Nota; Alexander Keller; Francisco Encinas‐Viso; Laura Parducci; Rodney T. Richardson; Richard M. Leggett; Berry J. Brosi; Kevin S. Burgess; Yoshihisa Suyama; et al. (Molecular Ecology, 2023)
Anthropogenic activities are triggering global changes in the environment, causing entire communities of plants, pollinators and their interactions to restructure, and ultimately leading to species declines. To understand the mechanisms behind community shifts and declines, as well as monitoring and managing impacts, a global effort must be made to characterize plant–pollinator communities in detail, across different habitat types, latitudes, elevations, and levels and types of disturbances. Generating data of this scale will only be feasible with rapid, high‐throughput methods. Pollen DNA metabarcoding provides advantages in throughput, efficiency and taxonomic resolution over traditional methods, such as microscopic pollen identification and visual observation of plant–pollinator interactions. This makes it ideal for understanding complex ecological networks and their responses to change. Pollen DNA metabarcoding is currently being applied to assess plant–pollinator interactions, survey ecosystem change and model the spatiotemporal distribution of allergenic pollen. Where samples are available from past collections, pollen DNA metabarcoding has been used to compare contemporary and past ecosystems. New avenues of research are possible with the expansion of pollen DNA metabarcoding to intraspecific identification, analysis of DNA in ancient pollen samples, and increased use of museum and herbarium specimens. Ongoing developments in sequencing technologies can accelerate progress towards these goals. Global ecological change is happening rapidly, and we anticipate that high‐throughput methods such as pollen DNA metabarcoding are critical for understanding the evolutionary and ecological processes that support biodiversity, and predicting and responding to the impacts of change.

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

Metabarcoding-based dietary analysis of hen harrier (Circus cyaneus) in Great Britain using buccal swabs from chicks - Kevin Nota; Stephen Downing; Arati Iyengar (Conservation Genetics, 2019)